(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Aim of present work is development and validation of advance derivative spectroscopic method for estimation of Montelukast (MON) and Bilastine (BIL) in their tablet dosage form. This tablet dosage form is used as an anti-asthmatic and allergic rhinitis. The developed method can be applied for simultaneous estimation of Montelukast and Bilastine in their combined dosage form. For this advanced derivative method, the absorbance at 226.8 nm (ZCP of Montelukast) and 326.4 nm (ZCP of Bilastine) was used for the estimation of Montelukast and Bilastine, respectively. The developed method is validated by ICH Q2R1 guidelines with validation parameters like linearity, LOD, LOQ, accuracy, precision, robustness, ruggedness and assay were performed using this guidelines. The method was found to be linear in the concentration range of 2-14 µg/ml for Montelukast (R2=0.999) and 4-28 µg/ml for Bilastine (R2=0.9997). LOD and LOQ found 0.1216 and 0.3686 for MON and 0.3406 and 1.0320 for BIL. Precision study were carried out by comparing on 3 different concentrations and result of their %RSD were <2%. Robustness study carried out by change in scanning speed and change in methanol manufacturer and Ruggedness study carried out by different analyst. Assay study was performed using tablet formulation. The developed method was utilized for simultaneous estimation of Montelukast and Bilastine for its tablet dosage form.